Regorafenib Regulates AD Pathology, Neuroinflammation, and Dendritic Spinogenesis in Cells and a Mouse Model of AD - Kyung-Min Han; Ri Jin Kang; Hyongjun Jeon; Hyun-ju Lee; Ji-Soo Lee; HyunHee Park; Seong Gak Jeon; Kyoungho Suk; Jinsoo Seo; Hyang-Sook Hoe (Cells, 2020)
The oral multi-target kinase inhibitor regorafenib, which targets the oncogenic receptor tyrosine kinase (RTK), is an effective therapeutic for patients with advanced gastrointestinal stromal tumors or metastatic colorectal cancer. However, whether regorafenib treatment has beneficial effects on neuroinflammation and Alzheimer’s disease (AD) pathology has not been carefully addressed. Here, we report the regulatory function of regorafenib in neuroinflammatory responses and AD-related pathology in vitro and in vivo. Regorafenib affected AKT signaling to attenuate lipopolysaccharide (LPS)-mediated expression of proinflammatory cytokines in BV2 microglial cells and primary cultured microglia and astrocytes. In addition, regorafenib suppressed LPS-induced neuroinflammatory responses in LPS-injected wild-type mice. In 5x FAD mice (a mouse model of AD), regorafenib ameliorated AD pathology, as evidenced by increased dendritic spine density and decreased Aβ plaque levels, by modulating APP processing and APP processing-associated proteins. Furthermore, regorafenib-injected 5x FAD mice displayed significantly reduced tau phosphorylation at T212 and S214 (AT100) due to the downregulation of glycogen synthase kinase-3 beta (GSK3β) activity. Taken together, our results indicate that regorafenib has beneficial effects on neuroinflammation, AD pathology, and dendritic spine formation in vitro and in vivo.